High proton conduction in an excellent water-stable gadolinium metal–organic framework - Xing, Xiu-Shuang; Fu, Zhi-Hua; Zhang, Ning-Ning; Yu, Xiao-Qing; Wang, Ming-Sheng; Guo, Guo-Cong (Chemical communications (Cambridge, England), 2019)
A new metal–organic framework with excellent water stability, {H[(N(CH 3 ) 4 ) 2 ][Gd 3 (NIPA) 6 ]}·3H 2 O (1, H 2 NIPA = 5-nitroisophthalic acid), displays a proton conductivity of 7.17 × 10 −2 S cm −1 (at 75 °C and 98% relative humidity), which is among the highest values for proton-conducting MOFs.